# Let f(x) = 4x - 5 and g(x) = 6x - 3. Find f(x) - g(x).

The relationship between independent and dependent variables is defined by the function. It is denoted by f(x).

## Answer: The value of f(x) - g(x) is - 2(x + 1) for the given functions f(x) = 4x - 5 and g(x) = 6x - 3.

Let's find the value of f(x) - g(x).

**Exaplanation:**

We know that (f - g)(x) = f(x) - g(x)

The domain of f(x) - g(x) consists of the values of x that are in the domain of f and the domain of g.

Given functions are f(x) = 4x - 5 and g(x) = 6x - 3

f(x) - g(x) = (4x - 5) - (6x - 3)

= 4x - 6x - 5 + 3

= -2x - 2

= -2(x + 1)